Complication Rates in Early Versus Late Cranioplasty—A 14-Year Single-Center Case Series. Issue 4 (19th January 2021) - Tora, Muhibullah S; Malcolm, James G; Mahmooth, Zayan; Pujari, Amit; Rindler, Rima S; Boulis, Nicholas M; Pradilla, Gustavo; Grossberg, Jonathan A; Ahmad, Faiz U
Abstract: BACKGROUND: Cranioplasty (CP) following decompressive craniectomy (DC) is a common neurosurgical procedure for cranial cosmesis and protection. There is uncertainty regarding the complication rates and potential benefits related to the timing of CP. OBJECTIVE: To investigate the impact of the timing of CP on complication rates for different etiologies of DC. METHODS: A retrospective chart review was performed of all CP cases between 2004 and 2018 for traumatic and nontraumatic indications of DC. Demographics, clinical characteristics, and complications were collected. Early and late CP were defined as replacement of the bone flap at ≤90 and >90 d following DC, respectively. RESULTS: A total of 278 patients were included, receiving 81 early and 197 late CPs. When analyzing all patients, early CP was associated with a statistically significant higher odds of any complication (odds ratio [OR]: 3.25, P  < .001), reoperation (OR: 2.57, P  = .019), hydrocephalus (OR: 6.03, P  = .003), and symptomatic extra-axial collections (OR: 9.22, P  = .003). Subgroup analysis demonstrated statistically significant higher odds of these complications only for the CP trauma subgroup, but not the nontrauma subgroup. The odds of complications postCP demonstrated a statistically significant decrease of 4.4% for each week after DC (Unit Odds Ratio [U-OR]: 0.956, P  = .0363). CONCLUSION: In our retrospective series, early CP was associated with higher odds of postoperative complications compared to late CP in the trauma subgroup. Greater care should be taken in preoperative planning and increased vigilance postoperatively for complications with this potentially more vulnerable subpopulation. Future prospective controlled trials are needed to elucidate optimal timing for CP. Graphical Abstract: